2019
DOI: 10.1016/j.aott.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Association of quadriceps angle with plantar pressure distribution, navicular height and calcaneo-tibial angle

Abstract: Objective The aim of study was to analyze the association between Quadriceps Angle (QA) and plantar pressure, navicular height (NH), and calcaneo-tibial angle (CTA). Methods A total of 64 volunteers (mean age: 22.25 ± 2.54 (range:19–33)) participated in this cross sectional study. EMED-m (Novel GmbH, Germany) electronic pedobarograph was employed for dynamic plantar pressure measurement using two step protocol. The angle between the vertical axis of calcaneus and the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Q-angle is the most common and simple assessment indicator for the clinical assessment of patellofemoral instability and patellar subluxation [10,24]. In previous studies, we found that arthroscopic GMC release could significantly reduce the Q-angle of GMC patients, thereby improving patellofemoral instability [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Q-angle is the most common and simple assessment indicator for the clinical assessment of patellofemoral instability and patellar subluxation [10,24]. In previous studies, we found that arthroscopic GMC release could significantly reduce the Q-angle of GMC patients, thereby improving patellofemoral instability [7].…”
Section: Discussionmentioning
confidence: 99%
“…Q-angle represents the supplementary angle of the angle between the line connecting the anterior superior iliac spine and the midpoint of the patella and the line connecting the tibial tubercle and the midpoint of the patella [10] (Figure 1(D2)). GMC patients are usually unable to squat down while closing their knees together, and a certain distance between the feet was required for the patient to squat down completely.…”
Section: Measurement Of Clinical Parametersmentioning
confidence: 99%
“…Multiple factors have been found to influence the magnitude of the QA measurement. Mainly, the state of the quadriceps muscle contraction [ 33 ] and anatomical characteristics [ 21 , 34 , 35 ] can influence the magnitude of the QA. As all lower limb alignments were measured in a standing position, the participants were encouraged to stand with their weight equally distributed between legs.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor influencing the Q angle is deformities observed in the ankle ( 15 ). Elvan et al ( 35 ) reported that the foot tended to pronate and the amount of load carried in the medial side increased with an increase in the Q angle, whereas a decrease in the Q angle caused supination in the foot and greater load in the lateral side. In addition, they reported that the most important marker influencing the Q angle was navicular height.…”
Section: Discussionmentioning
confidence: 99%